The Effect of E-Wom, Lifestyle, and Social Media Marketing on Purchase Intention with Trust as an Intervening Variable in Skincare for Male Gen Z - Manikasanti, Luh Gede Mas Putri; Suardana, Ida Bagus Raka (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Understanding the influence of e-WOM, lifestyle, and social media marketing and building trust can help increase purchase intention and market products better. This study aimed to investigate how lifestyle, social media marketing, and trust and purchase intention of MS Glow Men products are influenced by Gen Z teenagers in Denpasar City. There is no interest in buying this product, according to survey data. The results showed that E-WOM marketing, lifestyle, and social media positively and significantly affect trust and purchase intention. In addition, trust acts as a mediating variable that strengthens the influence of E-WOM and lifestyle on purchase intention. Thus, marketing strategies that focus on increasing consumer trust should focus on increasing consumer trust in MS Glow Men products.